2015
DOI: 10.1017/s1478951515000632
|View full text |Cite
|
Sign up to set email alerts
|

Development of an existential support training program for healthcare professionals

Abstract: Existential and spiritual issues are very important to severely ill patients, and healthcare professionals need to be attentive to such questions. It is important that professionals be properly prepared when patients need this communication. An evidence-based training intervention could provide such preparation. Healthcare staff were able to identify situations where existential issues were apparent, and they reported that their confidence in communication about existential issues increased after attending a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…Recently, interest has intensified in perceptions of meaning or purpose in life and their associations with health outcomes among patients with cancer and survivors. [1][2][3] A sense of meaning and purpose in life refers to the extent to which people perceive the world to be understandable, feel committed to and motivated by valued goals, and experience their existence as significant in the larger scheme of the world (ie, they matter). 4 Maintaining a sense that life is meaningful may help people to manage distress and enhance their quality of life and physical health.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interest has intensified in perceptions of meaning or purpose in life and their associations with health outcomes among patients with cancer and survivors. [1][2][3] A sense of meaning and purpose in life refers to the extent to which people perceive the world to be understandable, feel committed to and motivated by valued goals, and experience their existence as significant in the larger scheme of the world (ie, they matter). 4 Maintaining a sense that life is meaningful may help people to manage distress and enhance their quality of life and physical health.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study concerning current approaches (Galushko et al, 2015), the importance of self-protection and perceived professional expertize was highlighted. The additional conducted literature search showed that a main aim of the reported trainings was the ability to communicate confidently with the patients about existential issues, which might include a DD (Frommelt, 1991; Morita et al, 2014; Udo et al, 2014; Henoch et al, 2015). Other important learning outcomes were the ability to communicate attentively and compassionately, to explore factors fostering a DHD, to share solutions, to honor patients’ perceptions, to reflect one's attitudes toward existential issues (Strang et al, 2014; Henoch et al, 2015), and to cope with own emotions (Strang et al, 2014; Henoch et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were quasiexperimental[ 4 32 33 34 ] three studies were mixed method,[ 21 35 36 ] and the rest were randomized clinical trials. [ 5 21 36 37 38 39 ] These studies had two groups of intervention and control,[ 4 5 33 35 39 ] only one study was conducted on three intervention groups without a control. [ 36 ] The sample size varied in different studies from 28 nurses[ 40 ] to 149 nurses.…”
Section: Resultsmentioning
confidence: 99%